Developing Countries' Attractiveness for Foreign Direct Investment - Debt Overhang and Sovereign Risk as Major Impediments? (The Pakistan Development Review, 1991)
With declining debt inflows, foreign direct investment (FDI) has again become one of the major pillars of private financial flows to developing countries (Des). This has created some expectation to replace private bank olending by FDI. However, many heavily indebted countries may not only be constrained in terms of new private lending, but also in terms of FDI inflows. In order to overcome constraints in the supply of FDI, the determinants of FDI flows have to be identified in the first place. This has been done by the Kiel Institute of World Economics in a comprehensive study commissioned by the World Bank. The present paper summarizes some of the major results for details, see Agarwal et aZ. (1991). The focus is on the impact of sovereign risk on FDI and on possible disincentives for FDI arising from a debt overhang, i.e. on those aspects that reflect the most important recent changes in international capital market conditions. The empirical analysis concentrates on the 1980s. Regressions are run for an overall sample of about 35 host Des and for various subgroups. The paper is organized as follows. Section II presents the major hypotheses. The empirical results are summarized in Sections III and IV. Finally, some policy conclusions are drawn in Section V.